Discovery of New Antibacterial Peptide from Trypsin Hydrolysate of Monocled Cobra (Naja kaouthia) Venom Protein using C18 SPE Column and LC-HRMS - Erlista, Garnies Putri; Raharjo, Slamet; Raharjo, Tri Joko (Journal of Multidisciplinary Applied Natural Science, 2026)
Antimicrobial peptides (AMPs), as new antibiotic candidates, have the potential to treat infectious diseases. Peptides from N. kaouthia venom proteins can be used to produce AMP. The aim of this study was to identify the antibacterial potential of peptides derived from N. kaouthia venom protein purified by a reverse-phase solid-phase extraction column (SPE C18). N. kaouthia venom protein was isolated using Amicon® Ultra-15 with a 3000 Da centrifugal filter and then hydrolyzed using trypsin. The hydrolyzate was fractionated using reverse-phase (SPE C18), and the resulting fraction was tested for its antibacterial activity against S. aureus (Gram-positive) and E. coli (Gram-negative) bacteria. The most active fraction as an antibacterial was analyzed by high-resolution mass spectrometry (HRMS). The results showed that the 50% methanol fraction was active against E. coli bacteria, and the 100% methanol fraction was active against S. aureus. There are seven peptides identified, namely TVPVKR, TTMMNMLK, WWSDHR, SSLLVK, NSLLVK, LIPIASK, and GALMLK, which are responsible for the activity of the 50% methanol fraction. Meanwhile, there are two peptides, namely SSLLVK and NSLLVK, responsible for the activity of the 100% methanol fraction. LIPIASK and GALMLK peptides are predicted to show better potential as antimicrobial peptides.